Perceived New Normal and Inner Strength on Quality of Life in Breast Cancer Patients Receiving Adjuvant Endocrine Therapy - Sujin Ha; Eunjung Ryu (Elsevier, 2021)
Objective: This study aimed to investigate the differences in symptom experience, inner strength, adherence, and quality of life (QOL) according to the perception of the new normal, and identify the factors related to the QOL of breast cancer patients undergoing adjuvant hormonal therapy based on the theory of inner strength in women. Methods: This cross-sectional study recruited patients with breast cancer receiving adjuvant hormonal therapy in the National Cancer Center. Demographic and clinical characteristics were recorded, and patients were assessed using the M. D. Anderson Symptom Inventory, Connor-Davidson Resilience Scale 2, Morisky Medication Adherence Scale 8, and Functional Assessment of Cancer Therapy-General Scale. Results: After the breast cancer diagnosis, the perception of the new normal showed a significant dependence on pill count and emotional and functional well-being. The hierarchical regression analysis indicated that the new normal, symptom interference, and inner strength after adjusting for age, time since diagnosis, and receiving chemotherapy were significant predictors of QOL in breast cancer patients receiving adjuvant endocrine therapy. The model accounted for 47.8% of the variance in QOL. Conclusions: The theory of inner strength might be a potential pathway in health care to improve patients' QOL during long-term medication. The results of this study have both theoretical and applied implications. The findings can be utilized as evidence for developing an effective intervention that improves the QOL and adherence to adjuvant hormonal therapy of breast cancer patients.